Effect of fatigability on sprint time performance and force-velocity profile according to maturity status in young rugby players - Galantine, P.; Sudlow, A.; Hays, A.; Maso, F.; Duché, P.; Bertin, D. (PLOS ONE, 2025)
Little is known about the influence of fatigue in repeated overground sprinting on force-velocity properties in children and adolescents, while this ability to repeat sprints is important for future progress in rugby union. Sprint time decline is commonly used to assess fatigability. However, it does not provide data on biomechanical aspects of sprint performance such as maximal power, force, and velocity production. As sprint time performance and force-velocity properties do not linearly change during adolescence, considering maturity status is important. This study aimed to assess the effect of fatigue on sprint time performance fatigability, force-velocity parameters, and mechanical effectiveness according to maturity status. A group of fifteen boys (12.5 ± 0.5 years) children and a group of seventeen boys (15.1 ± 0.6 years) adolescent rugby players completed seven blocks, consisting of a 30-meter sprint followed by five minutes of high-intensity exercise with one minute of passive recovery. The force-velocity parameters were calculated at each sprint, and performance decrement was assessed using a fatigue index. A main effect of block repetition was found for maximal power output, maximal force, maximal velocity, 30-meter sprint time, fatigue index and mechanical effectiveness parameters with large effect sizes (p <0.001; = 0.19 to 0.47) and without a main effect of maturity status (p = 0.37 to 0.99; = 0.00 to 0.05). This could be explained by the modalities (duration, intensity, recovery) of the protocol and the training level of the adolescent group. For both groups, the decrease in maximal power output was due more to a reduction in maximal velocity than force, and mechanical effectiveness was negatively impacted. Coaches could prioritize the training of horizontal force at high velocity under fatigue conditions, as this ability tends to be the most affected. They could also incorporate training on mechanical effectiveness as this is a determinant in team sports.